Microannulus Formation Mechanism at the Cementing Interface of a Thermal Recovery Well during Cyclic Steam Injection - JiWei Wu; XueGang Wang; Lin Song; ShouMing Zhong; WenFeng Yin (Advances in Civil Engineering)
During the thermal recovery of heavy oil when using cyclic steam injection technology, a microannulus tends to form at the cementing interface subjected to high temperature and pressure during steam injection, and large temperature and pressure differences after injection can lead to wellbore integrity failure. In this study, a thermomechanical coupled finite element casing-cement-formation model of a thermal recovery wellbore is established. The deformation of the wellbore during both the steam injection stage and the steam shutdown stage is analyzed. The microannulus formation mechanism at the cementing interface of the wellbore is studied. During steam injection, under the large thermomechanical coupling load, the wellbore generates a high stress that leads to elastic-plastic deformation. In the steam shutdown stage, with the load on the wellbore decreasing, elastic deformation recovers mostly, while plastic deformation continues. If the plastic deformation is large enough, a microannulus will form at the cementing interface. Increasing the elastic moduli of the casing, cement, and the formation can enlarge their plastic deformation during steam injection. The increase of plastic deformation of the cement or formation can enlarge the microannulus of the casing-cement interface or the cement-formation interface correspondingly in the steam shutdown stage.